Impact of Thin-Walled Projectiles with Concrete Targets - Rayment E. Moxley; Mark D. Adley; Bob Rohani (Shock and Vibration)
An experimental program to determine the response of thin-walled steel projectiles to the impact with concrete targets was recently conducted. The projectiles were fired against 41-MPa concrete targets at an impact velocity of 290 m/s. This article contains an outline of the experimental program, an examination of the results of a typical test, and predictions of projectile deformation by classical shell theory and computational simulation. Classical shell analysis of the projectile indicated that the predicted impact loads would result in circumferential buckling. A computational simulation of a test was conducted with an impact/penetration model created by linking a rigid-body penetration trajectory code with a general-purpose finite element code. Scientific visualization of the resulting data revealed that circumferential buckling was induced by the impact conditions considered.